Pengaruh Pengangguran Terhadap Tingkat Kemiskinan Di Provinsi Jambi (2017-2021) - Mipratul Jannah; Novi Mubyarto; Ahmad Syahrizal (JOURNAL SAINS STUDENT RESEARCH, 2023)
Jambi Province is one of the regions in Indonesia that continues to face the problem of poverty. Poverty can be seen as a condition of society with a weak economic level. This poverty is also affected by unemployment. This was examined by Cutler and Katz and Fowers found that the unemployment rate is positively related to the number of people below the poverty line or in other words the higher the unemployment rate, the greater the poverty rate. This study aims to determine the effect of unemployment on the level of poverty in the province of Jambi, the method is used descriptive quantitative, with data collection techniques in this study using documentation techniques. Based on the research that has been done, the results can be concluded as follows: The results in this study are that in 2017 to 2021 unemployment has a positive and significant effect on poverty in Jambi.